The Impact of Organisational Values on the Commercialisation of NGOs: Evidence Based on the Management by Values Theory - Mikołajczak, Paweł (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
This study aims to identify the impact of organisational values on the commercialisation of Polish NGOs. The commercialisation of NGOs is seen as the market methods adoption process of managing, providing services and social mission fulfilling. Values expressed through social missions are the most important reference points and core of NGO management. As non‑profit organisations are usually viewed as value‑based organisations with their identity rooted in meeting community needs, they cultivate a culture of trust by shaping and strengthening beliefs and values among their stakeholders. Although there is an intense discussion in the literature on the commercialisation of non‑profits, the relationships between organisational values and commercialisation of non‑governmental organisations have been poorly empirically verified thus far. Hence the identification of these relationships is an added value of this article. Based on a representative survey of 1,300 national NGOs, a logistic regression analysis was conducted. Identifying with the use of this method the probability of commercialisation of non‑profits as a result of the adaptation of specific organisational values is a new approach which is an original contribution of this work to current research in this area. It has been found that survival values significantly influence the commercialisation of NGOs. The study indicates that conservative values have a decreasing impact on the probability of NGO commercialisation, while entrepreneurial values stimulate this impact. The results also contribute to the theory of Management by Values, on the basis of which the theoretical framework of the article was defined and hypotheses were formulated.